The use of Puppets in the educational process of Scientific topics, Like physics " Archimedes Principle as a typical example " (Al-Academy, 2017)
This Study presents and provides Variable thoughts and aspects for representing Scientific topics " Physics for instance " as Play Shows for high School Students, by Showing a suggested Method that will Contribute in illustrating the Steps of writing the educational Scientific topic, and this method will help teachers to deliver their message to the Students " receivers " easily.The researcher have used Puppets in this method as the assisting tool for teachers, to help them deliver message Clearlym easily and Joyful.The researcher in his experiment used " Archimedes Principle " as a typical example, by Converting it into a theatrical Script, with respect to the Concept of Science, and in accordance to the Scientific educational Curriculum